Cultural impact assessment: a systematic literature review of current methods and practice around the world*. Issue 1 (2nd January 2016) - Partal, Adriana; Dunphy, Kim
Abstract: In the past decades, culture has increasingly been accepted as a dimension to be planned and managed within public policy, alongside social, economic and ecological considerations. Techniques for impact assessment of interventions on our economy, ecology and society are becoming more sophisticated, but are not yet well established within the cultural domain. This paper presents the results of a systematic literature review on applications of cultural impact assessment (CIA) internationally. Findings indicate that CIA has largely been practiced since 2002 to understand the impact of development processes on indigenous communities. While interest in CIA was also apparent in areas of public policy, particularly local government, little evidence was found of the practice actually established. A divergent understanding of CIA was found in the 'cultural' (funded arts and heritage) sector where it was understood as both impact on culture, but also impact of cultural activities. Only two developed tools for measuring cultural impact were found, one each for indigenous contexts and cities. Recommendations for strengthening CIA practice include establishing agreed definitions of culture and cultural impact, and validated tools, including measurement frameworks and indicators.